The occurrence of postsynaptic alpha- and beta-adrenoceptors in the guinea-pig gall bladder. - Doggrell, S. A. (Nature Publishing Group, 1980)
1 Guinea-pig gall bladder strips were contracted by (-)-noradrenaline, 10(-5) M, and by field stimulation at 5 Hz (in the absence or presence of 10(-6) M atropine) and relaxed to 10(-5) M (-)-isoprenaline. (-)-Adrenaline, 10(-5) M, predominantly contracted, but sometimes relaxed, this preparation. 2 In the presence of 10(-6) M phentolamine, contractions to (-)-noradrenaline and to (-)-adrenaline were reversed to relaxations. The relaxations produced by (-)-isoprenaline were unaltered. In the presence of 10(-6) M propranolol, contractions to (-)-noradrenaline increased in magnitude, relaxations to (-)-adrenaline were reversed to contractions, and relaxations to (-)-isoprenaline were abolished. These results demonstrate the presence of postsynaptic alpha-adrenoceptors which mediate contractions, and postsynaptic beta-adrenoceptors which initiate relaxations, in the guinea-pig gall bladder. 3 The contractile responses to continuous field stimulation for 5 min at 5 Hz in Krebs solution alone were reduced in magnitude by propranolol, 10(-6) M. In the presence of 10(-6) M atropine (added to eliminate the cholinergic component of the response), propranolol, 10(-6) M, had no effect on responses to stimulation at 5 Hz. Thus propranolol reduced the response to cholinergic stimulation in this tissue; the basis of this effect is unclear. In the absence or presence of atropine (10(-6) M), the responses to 5 Hz were smaller in magnitude in the presence than absence of phentolamine, 10(-6) M. This suggests that the responses to field stimulation of the guinea-pig gall bladder may, in part, be due to the release of endogenous noradrenaline which acts at postsynaptic alpha-adrenoceptors.